A comparative study of three conference rooms of three advertising agencies - Sales, Aurora Sarah V.; Florendo, Raquel Baltazar (1990.)
(NO ABSTRACT PROVIDED BY THE AUTHOR)
Thesis (BID)--University of the Philippines Diliman.
Keywords: Conference rooms -- Philippines; Advertising agencies -- Philippines